A new respiratory monitoring and processing system based on Wii remote: Proof of principle. Issue 7 (13th June 2013) - Peng, Y.; Vedam, S.; Gao, S.; Balter, P.
Abstract : Purpose: : To create a patient respiratory management system and patient self‐practice tool using the Wii remote, a widely available consumer hardware product. Methods: : The Wii remote (Wiimote) (Nintendo, Redmond, WA) contains an infrared (IR) camera that can track up to four spots whose coordinates are reported to a host computer via Bluetooth. The Wiimote is capable of tracking a fiducial box currently used by a commercial monitoring system [Real‐time Position Management TM (RPM) system, Varian Associates, Palo Alto, CA], if the correct IR source is used. The authors validated the Wiimote tracking by comparing the amplitude and frequency of signals among those reported by Wiimote with known movements from an inhouse servo‐driven respiratory simulator, as well as with those measured using the RPM. The simulator comparison was done using standard sinusoid signals with amplitude of 2.0 cm as well as recorded patient respiratory traces. The RPM comparisons were done by simultaneously recording the RPM reflective box position with the Wiimote and the RPM. Timing was compared between these two systems by using the digital beam‐on signal from the CT scanner, for the 4DCT to synchronize these acquisitions. Results: : The data acquisition rate from the Wiimote was 100.0 ± 0.4 Hz with a version 2.1 Bluetooth adaptor. The standard deviation of the height of the motion extrema was 0.06 and 1.1 mm when comparing those measured by the Wiimote and the servomotor encoder for standard sinusoid signal and prerecorded patient respiratory signal, respectively. The standard deviation of the amplitude of motion extrema between the Wiimote and RPM was 0.9 mm and the timing difference was 253 ms. Conclusion: : The performance of Wiimote shows promise for respiratory monitoring for its faster sampling rate as well as the potential optical and GPU abilities. If used with care it can deliver reasonable spatial and temporal accuracy.